Schubert and Beethoven - Adorno’s early antipods of the music in bougeois epoch - Jeremić-Molnar Dragana; Molnar Aleksandar (Filozofija i Društvo, 2012)
In this article the authors are reconstructing the dichotomies which the young Theodor Adorno was trying to detect in the music of the bourgeois epoch and personify in two antipodes - Franz Schubert and Ludwig van Beethoven. Although already a devotee of Arnold Schönberg and the 20th century music avantgardism, Adorno was, in his works prior to his exile from Germany (1934), intensively dealing with Schubert and his opposition towards Beethoven. While Beethoven was a bold and progressive revolutionary, fascinated by the “practical reason” and the mission to rise up and reach the stars, Schubert wanted none of it (almost anticipating the failure of the whole revolutionary project). Instead, he was looking backwards, to primordial nature and the possibility of man to participate in its mythic cycles of death and regeneration. The lack of synthesis between this two opposing tendencies in the music of early bourgeois epoch lead to the “negative dialectics” of Schönberg and 20th century music avantgardism and to the final separation of Beethovenian musical progress and Schubertian musical mimesis. [Projekat Ministarstva nauke Republike Srbije, br. 177019: Identiteti srpske muzike u svetskom kulturnom kontekstu, i br. 179035: Izazovi nove društvene integracije u Srbiji - koncepti i akteri]